Stability for the Systems of Ordinary Differential Equations with Caputo Fractional Order Derivatives - Taher , Asad J.; Fadhel , Fadhel S.; Hasan, Nabaa N. (Iraqi Journal of Science, 2022)
Fractional calculus has paid much attention in recent years, because it plays an essential role in many fields of science and engineering, where the study of stability theory of fractional differential equations emerges to be very important. In this paper, the stability of fractional order ordinary differential equations will be studied and introduced the backstepping method. The Lyapunov function is easily found by this method. This method also gives a guarantee of stable solutions for the fractional order differential equations. Furthermore it gives asymptotically stable.